2018
DOI: 10.1002/jlcr.3687
|View full text |Cite
|
Sign up to set email alerts
|

Radiosynthesis of an 18F‐fluoroglycosylated aminoferrocene for in‐vivo imaging of reactive oxygen species activity by PET

Abstract: The imaging of reactive oxygen species (ROS) at the molecular level with high sensitivity and specificity by positron emission tomography (PET) could be of enormous interest to increase our knowledge about ROS activity and signalling, especially in tumours. The aim of this research was to optimise the click chemistry‐based radiosynthesis of an 18F‐labelled aminoferrocene glycoconjugate that was derived from an N‐alkylaminoferrocene lead structure known to have anticancer activity in vitro. Applying the solvent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
(38 reference statements)
1
14
0
Order By: Relevance
“…Noteworthily, the purification of the 18 F-labeled aminoferrocene glycoconjugate was problematic, since the hydrolysis of the boronic acid ester and oxidation of non-carrier-added 26 occurred in the buffered solution. However, the RCY (referred to the CuAAC reaction) of carrier-added 26 was 85% under optimized conditions [55]. Further PET studies in PC3 and AR42J tumor-bearing mice demonstrated that carrier-added 26 showed a 2−3-fold higher tumor uptake at 45-60 min p.i.…”
Section: -Deoxy-6-[ 18 F]fluoro-β-glycosyl Azides For Click Chemistry-based 18 F-fluoroglycosylationmentioning
confidence: 97%
See 1 more Smart Citation
“…Noteworthily, the purification of the 18 F-labeled aminoferrocene glycoconjugate was problematic, since the hydrolysis of the boronic acid ester and oxidation of non-carrier-added 26 occurred in the buffered solution. However, the RCY (referred to the CuAAC reaction) of carrier-added 26 was 85% under optimized conditions [55]. Further PET studies in PC3 and AR42J tumor-bearing mice demonstrated that carrier-added 26 showed a 2−3-fold higher tumor uptake at 45-60 min p.i.…”
Section: -Deoxy-6-[ 18 F]fluoro-β-glycosyl Azides For Click Chemistry-based 18 F-fluoroglycosylationmentioning
confidence: 97%
“…Tracers for imaging the content of reactive oxygen species (ROS) in tumors could be valuable for PET imaging of tumors and contribute to our knowledge of the biodistribution of anticancer drug candidates that are ROS-dependently trapped in tumor cells [54]. A click chemistry-based 18 F-fluoroglycoconjugation of N-alkylaminoferrocene as a potential anticancer agent was optimized by Toms et al, employing 14 and Cu(OAc) 2, phosphate buffer/THF, and sodium ascorbate for the CuAAC reaction conditions [55]. Noteworthily, the purification of the 18 F-labeled aminoferrocene glycoconjugate was problematic, since the hydrolysis of the boronic acid ester and oxidation of non-carrier-added 26 occurred in the buffered solution.…”
Section: -Deoxy-6-[ 18 F]fluoro-β-glycosyl Azides For Click Chemistry-based 18 F-fluoroglycosylationmentioning
confidence: 99%
“…Noteworthy, the purification of the 18 F-labeled aminoferrocene glycoconjugate was problematic, since hydrolysis of the boronic acid ester and oxidation of non-carrier-added 26 occurred in buffered solution. However, the RCY (referred to the CuAAC reaction) of carrier-added 26 was 85% under optimized conditions [56]. Further PET studies in PC3 and AR42J tumor-bearing mice demonstrated that carrier-added 26 showed a 2−3-fold higher tumor uptake at 45-60 min p.i.…”
Section: -Deoxy-2-[ 18 F]fluoro-β-glucosyl Azide For Click Chemistry Based 18 F-fluoroglycosylationmentioning
confidence: 97%
“…Tracers for imaging the content of reactive oxygen species (ROS) in tumors could be valuable for PET imaging of tumors and contribute to our knowledge of the biodistribution of anticancer drug candidates that are ROS-dependently trapped in tumor cells [55]. A click chemistry based 18 F-fluoroglycoconjuation of N-alkylaminoferrocene as a potential anticancer agent was optimized by Toms et al, employing 14 and Cu(OAc)2, phosphate buffer/THF, and sodium ascorbate for the CuAAC reaction conditions [56]. Noteworthy, the purification of the 18 F-labeled aminoferrocene glycoconjugate was problematic, since hydrolysis of the boronic acid ester and oxidation of non-carrier-added 26 occurred in buffered solution.…”
Section: -Deoxy-2-[ 18 F]fluoro-β-glucosyl Azide For Click Chemistry Based 18 F-fluoroglycosylationmentioning
confidence: 99%
“…This compound was prepared by conjugation of 6‐deoxy‐6‐[ 18 F]fluoro‐β‐glucopyranosyl azide [6] via the reaction of copper(I)‐catalyzed azide−alkyne 1,3‐dipolar cycloaddition (CuAAC) [5] . The studies of the biodistribution of conjugate 2 in mice using PET provided first valuable insights into stability and tumor uptake of NAAF prodrugs in vivo [5,7] . However, their important limitation was the relatively short observation time.…”
Section: Introductionmentioning
confidence: 99%